A new species of Pachycara Zugmayer (Teleostei: Zoarcidae) from off Monterey Bay, California, USA, with comments on two North Pacific Lycenchelys species - Anderson, M. Eric (Zootaxa, 2012)
A new species of the eelpout genus Pachycara Zugmayer is described from the lower bathyal zone of central California,USA on the basis of three adult males. It is distinguished from its congeners mainly by its low vertebral counts, origin ofthe mediolateral branch of the lateral line system, lack of pelvic fins, presence of scales on the nape and cheeks and re-stricted gill slit. In addition, two species of the eelpout genus Lycenchelys Gill (L. micropora and L. monstrosa), taken in the same collection as the new Pachycara, are discussed, with the latter added to the California marine fish fauna.